(untitled) (Malay Literature, 2025)
Pantun is a traditional Malay poetic form that is widely known and appreciated within the Malay community. It is an original creation of the Malay people. Typically, pantun is used in various contexts, including customary ceremonies, celebrations or the expression of emotions. Moreover, pantun serves as a means of communication in the community due to its refined and beautiful language. It additionally plays an important role in preserving Malay culture and language. One of the mediums of pantun preservation is through its use in Malay films. This is because pantun in films plays an important role in preserving Malay culture and language, as well as showcasing its beauty, especially in classic Malay films that remain relevant and are still watched today. However, there is a research gap regarding pantun in films, prompting this study to be conducted specifically on the function and aesthetics of pantun in Malay films. Accordingly, this paper analyses the aesthetics and function of pantun in the film Gurindam Jiwa (1965), starring Nordin Ahmad and directed by M. Amin. This paper employs library research and the analysis of pantun in the film’s dialogue based on Malay Poetics by Muhammad Haji Salleh. The findings show the various functions of pantun in the film, including as a manifestation in the relationship between nature and humans, an expression of emotions and feelings, a form of entertainment, as well as a medium for satire and social criticism. Therefore, this paper proves that pantun in films possesses its own functions and aesthetics, especially in Malay films. This clearly shows that Malay films incorporate elements of pantun as a form of linguistic aesthetics and cultural sustainability. Full text: PDF